SIMD Image Resampling - WARPENBURG, M R; Siegel, L J (IEEE transactions on computers, 1982)
Due to advances in VLSI technology, large scale arrays of microprocessors forming parallel processing systems have become feasible. The use of such a microprocessor array operating in the SIMD (single instruction stream-multiple data stream) mode to perform image resampling is explored. A general theory of resampling in terms of offsets is developed. From this, an approach to performing resampling in an SIMD environment is given. Detailed analysis of the SIMD algorithm is presented, and computational speedup over conventional uniprocessor approaches is shown to be approximately a factor of N where N is the number of processors used.